2018
DOI: 10.1002/crat.201800138
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Morphological, and Electrochemical Corrosion Properties of TiO2 Formed on Ti6Al4V Alloys by Anodization

Abstract: In this work, TiO2 layers are synthetized on Ti6Al4V alloy substrate by electrochemical anodizing process in fluoride‐containing alkaline electrolytes and under different applied voltages (10, 20, and 30 V). The scanning electron microscopy (SEM) reveals a nearly regular and vertical alignment of TiO2 nanotubes (≈80–100 nm) for specimen treated at 20 V and an agglomerate of particles with no particular orientations for those specimens treated at 10 and 30 V. The X‐ray diffraction (XRD) indicates the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…It should be mentioned that a more positive corrosion potential results in higher corrosion resistance of the coating, confirming the Bare Ti6Al4V ELI transpedicular screw exhibits a pronounced increasing from −0.40 V/Ag/AgCl towards more positive values until it does not reach a constant value of OCP −0.337 V/Ag/AgCl in 1200 s in 0.9% NaCl. This phenomenon can be explained, as reported by Atmani et al [7], by the formation of a protective passive oxide film on the surface of the Ti6Al4V alloy. The as-anodized corresponding OCP plot behaves nearly the same as the substrate.…”
Section: Open Circuit Potential Measurementssupporting
confidence: 53%
See 1 more Smart Citation
“…It should be mentioned that a more positive corrosion potential results in higher corrosion resistance of the coating, confirming the Bare Ti6Al4V ELI transpedicular screw exhibits a pronounced increasing from −0.40 V/Ag/AgCl towards more positive values until it does not reach a constant value of OCP −0.337 V/Ag/AgCl in 1200 s in 0.9% NaCl. This phenomenon can be explained, as reported by Atmani et al [7], by the formation of a protective passive oxide film on the surface of the Ti6Al4V alloy. The as-anodized corresponding OCP plot behaves nearly the same as the substrate.…”
Section: Open Circuit Potential Measurementssupporting
confidence: 53%
“…To improve in vivo osteointegration, the Ti6Al4V ELI is subjected to surface treatments, such as nitriding, electropolishing, and electrochemical oxidation. Thermal oxidation [3] or plasma [4] is distinguished on the alloy surface from the processes of oxide layer production, but, more often, the anodic surface is subjected to anodizing [5][6][7][8]. The major advantages of the anodizing process are ability to control the fine-tuning of oxide film thickness, feature size, topography, and chemistry, as well as its simplicity, low-cost, ease of implementation, and scalability at the industrial level [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the pioneering efforts to utilize electrochemical anodization as an innovative approach for the surface modification of Ti-based alloys was performed by Dunn et al [ 221 , 222 ], where porous surface coatings are formed by anodization and incorporating antibiotics onto the oxide surface. Zwilling et al [ 223 ] also reported that anodization on Ti and Ti–6Al–4V alloys in the F − ion solution is an effective approach to attain tunable tubular oxide layers under different anodization conditions [ 16 , 17 , 65 , 133 , [224] , [225] , [226] , [227] , [228] , [229] , [230] , [231] , [232] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] , [246] , [247] , [248] , [249] , [250] , [251] , [252] , [253] , [254] , [255] , [256] , [257] , [258] , [259] , [260] , [261] , [262] ]. Since the Ti–6Al–4V alloy is a dual-phase alloy, the development kinetics of nanotubes are dissimilar for the α and β phases [ 69 ].…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…They found that the Ti–Al–V–O nanotubes are stable at a high temperature of 675 °C in the air without collapse, whereas the irregular Ti–Al–V–O nanopores have lower thermal stability, which is in good agreement with our findings [ 133 ]. Recently, Atmani et al [ 251 ] synthesized the MONs layer (~80–100 nm) on Ti–6Al–4V alloy using electrochemical anodization in fluoride containing alkaline solution and under different applied voltages (10, 20, and 30 V). Mansoorianfar et al [ 247 ] also studied the fabrication and characterization of nanotube arrays on the Ti–6Al–4V surface for the enhancement of cell treatment in biomedical applications.…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…Different surface engineering methods like PVD [5], CVD[6], plasma treatment [7], nitriding [8] and anodization [9] have been used to modify titanium alloys. Among them, ceramic conversion treatment (CCT) can generate a ceramic hard layer supported by a hardened diffusion zone on the surface of the titanium alloys which can greatly improve the tribological performance of titanium alloys [10].…”
Section: : Introductionmentioning
confidence: 99%